Pengaruh Merek Terhadap Kepuasan Pelanggan (Studi Kasus : Furniture Impor B&B Italia) - Margaretha Hillary (Universitas Tarumanagara, 2019)
The purpose of this research is to examine the effect of Brand which dimensions researched are Brand Image, Brand Equity, and Brand Personality, toward Customer Satisfaction. The population used for the research were users of B&B Italia furniture and domiciled in DKI Jakarta. The sample size for this research were 100 respondents. Data used in this research are primary data obtained from online questionnaire and secondary data obtained from books and journals and purposive sampling techniques was employed to process all the data. The analytical techniques that are used in this research are composed of multiple regression analysis using the t test, F test, and the coefficient of determination (R2). Data processing is using the SPSS ver. 25.0 for Windows. The results of this research show that there is a significant influence between Brand Image (X1) and Customer Satisfaction (Y) with the number of beta coefficient is 0.495. There is also a significant influence between Brand Equity (X2) and Customer Satisfaction (Y) with the number of beta coefficient is 0.241. And the last, there is a significant influence between Brand Personality (X3) and Customer Satisfaction (Y) with the number of beta coefficient is 0.175. Based on the coefficient of determination, the independent variables influenced by 60.1% toward the dependent variable and the rest is 39.9% was influenced by another variable which not investigated in this research.